Does the Transtheoretical Model of Behavior Change Provide a Useful Basis for Interventions to Promote Fruit and Vegetable Consumption?. Issue 6 (July 2013) - Horwath, Caroline C.; Schembre, Susan M.; Motl, Robert W.; Dishman, Rod K.; Nigg, Claudio R.
Purpose: To determine whether Transtheoretical Model (TTM) constructs differ between individuals making successful versus unsuccessful stage transitions for consumption of five or more servings of fruit and vegetables each day and thus provide a useful basis for designing health promotion interventions. Design: Longitudinal, observational study. A randomly selected, multiethnic cohort of adults assessed at 6-month intervals over 2 years. Setting: General community, Hawaii. Subjects: There were 700 participants (62.6% female; mean = 47 ± 17.1 years; 31.1% Asian, 22.1% Native Hawaiian/Pacific Islander, 35.0% Caucasian; 25.1% participation rate). Measures: Stage of readiness, experiential and behavioral processes of change, pros, cons, self-efficacy, and self-reported fruit and vegetable consumption. Analysis: The study used t-tests to determine which TTM variable scores differed consistently between those making "successful" versus "unsuccessful" stage transitions from precontemplation, preparation, and maintenance. Sample sizes for contemplation and action prohibited similar analyses. Results: Compared to those remaining in precontemplation, individuals successfully progressing from precontemplation showed significantly greater use of behavioral processes (collectively and self-liberation) and consciousness raising (p < .001). However, only self-liberation demonstrated significant differences consistently over time. Conclusion: This longitudinal investigation reveals that TTM behavioral processes, particularly self-liberation, predict successful transition out of precontemplation for adult fruit and vegetable consumption, suggesting that public health messages tailored according to these TTM variables may be effective for this group. However, for adults prepared to adopt or maintain fruit and vegetable consumption, tailoring based on variables from other theories is needed.